1994
DOI: 10.1111/j.1745-4522.1994.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Detectable Odor Thresholds of Selected Lipid Oxidation Compounds at Various Temperatures in a Gelatin Model System

Abstract: ABSTRACT. This study was undertaken to determine detection thresholds of selected volatile organics known to be produced during the oxidation of food lipids. Gelatin was chosen to simulate a complex thermally‐sensitive food system. Stock solutions of pentanal, hexanal, t‐2‐hexenal, heptanal, t‐2‐octenal, and t,t,‐2,4‐decadienal were prepared using distilled water. A gelatin (3%) dispersion was prepared with distilled water, cooled (22C) then organic stock solutions were added to it at parts per billion (ppb) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…DETECTION ODOR THRESHOLD DIFFERENCES were three orders of magnitude for pentanal, hexanal, t-2-hexenal, t-2-octenal, and two orders of magnitude for heptanal and t,t-2,4-decadienal in a beef system compared to the same compounds in a gelatin system (Vega and Brewer, 1994) (Table 1). Cooked beef DOT values ranged from 0.23 ppm for heptanal to 7.87 ppm for t-2hexenal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DETECTION ODOR THRESHOLD DIFFERENCES were three orders of magnitude for pentanal, hexanal, t-2-hexenal, t-2-octenal, and two orders of magnitude for heptanal and t,t-2,4-decadienal in a beef system compared to the same compounds in a gelatin system (Vega and Brewer, 1994) (Table 1). Cooked beef DOT values ranged from 0.23 ppm for heptanal to 7.87 ppm for t-2hexenal.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in odor detection thresholds of several lipid oxidation products (aldehydes) have been reported using different media (air, water, milk, vegetable oil, mineral oil, paraffin oil, and gelatin); odor thresholds differed widely among different media (Fazzalari, 1978;Lillard et al, 1962;Lillard and Powers, 1975;Salo, 1970;Vega and Brewer, 1994). These studies indicated the different degrees of variation the matrix may cause for odor thresholds.…”
Section: Introductionmentioning
confidence: 95%
“…In our study, the hexanal derived from n-6 fatty acids in modified oils increased from 0 to 7.3 to 189.1 to 316.4 ppm during a 96 h storage at 60°C. LA (n-6) may be expected to produce pentane, hexanal, malondialdehyde, octanal, and 2,4-decadienal upon oxidation (Vega and Brewer 1994). Shahidi and others (1987) found a direct relationship between hexanal content and sensory scores of cooked ground pork which contains a high amount of LA.…”
Section: Headspace Volatile Analysismentioning
confidence: 98%
“…Similarly, n-6 PUFA, especially LA, produce more of the 13-hydroperoxides as their primary product of oxidation and produce hexanal upon homolytic cleavage (37). LA, which is n-6, can be expected to produce pentane, hexanal, malondialdehyde, octanal, and 2,4-decadienal upon oxidation (38). Shahidi et al (39) found a direct relationship between hexanal content and sensory scores of cooked ground pork, which contains a high amount of LA.…”
Section: Resultsmentioning
confidence: 98%